Documentation Study of Street Children by Social Office of Padang City - Yoti Melindra; Irmawita Irmawita (Universitas Negeri Padang, 2020)
This study aims to describe and explain how the documentation study of street children by the Social Office of Padang City. This research uses a case study of qualitative research. Data sources used are primary data and secondary data obtained through interviews and documentation. The informants in this study were determined by purposive sampling, some of the research informants were the Head of Social Rehabilitation, Head of the Social Rehabilitation Section, Children and the Elderly in the Social Office of Padang City. Test the validity of the data using source triangulation techniques. Data analysis techniques were obtained from interviews and interpreted qualitatively, in the form of abstracts, words, and statements. The results showed that the study of street children's documentation by the Social Office of Padang City can be said to have been quite good and tried but not optimal in carrying out street children's coaching because there is still guidance that has not been well realized. In this program, street children are given four forms of guidance, namely mental, physical, social, and skill guidance but the guidance of skills has not been realized properly. This is due to the lack of cooperation between the Social Office of Padang City and the community so that the program seems unsustainable. The Social Office of Padang City conducted socialization to schools and to the community aimed at preventing the delinquency of children and warning all parents to continue to pay attention to their children and told all parents not to employ minors. In order to prevent children from going down the streets of the government through the Social Office of Padang City, they also provide assistance to street children both in the form of money and the necessities needed to open a business.Keywords: Social Office, Documentation Study, Street Children